A Rare Case of Pulmonary Neuroendocrine Carcinoma in Transfusion-dependent Thalassemia Patient: Clinical Presentation, Management, and Implications - Lia Sasmithae; Amaylia Oehadian; Dimmy Prasetya (Interna Publishing, 2024)
Transfusion-dependent thalassemia (TDT) is often accompanied by complications related to iron overload and the development of malignant solid tumors or hematological malignancies. The occurrence of Neuroendocrine carcinoma, specifically in the respiratory tract, is very rare, with a prevalence of approximately 25%. Therefore, this study presented a case of a 42-year-old male with a beta-thalassemia major at 28 years, complaining of shortness of breath. This case was reported due to its rarity in providing information about solid tumors in thalassemia patients. The physical examination revealed several symptoms, including tachycardia, tachypnea, anemia, icteric sclera, elevated jugular venous pressure, coarse wet Ronchi in the medial to basal areas of both lungs, hepatomegaly, and splenomegaly (Schuffner 4). The patient regularly received blood transfusions and iron chelation therapy. A thoracic CT scan showed a lung mass and a biopsy of the mass revealed Pulmonary Neuroendocrine Carcinoma with high-grade proliferation and, large cell type. The patient also passed through cisplatin-etoposide chemotherapy for 6 cycles every 21 days. There is almost no data on pulmonary neuroendocrine carcinoma in thalassemia patients, so it is hoped that this case report can provide information about malignant solid tumors that can occur in thalassemia patients.